KEBIJAKAN KRJMINAL DALAl\1 MENANGGULANGI KEJAHATAN PERDAGANGAN ANAK DI BAWAH UMUR - M. Chairul Idrah (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
Crimrnal pohcres m tackling traffickmg mmors is done by applying precaution (prevention), measures of protection  (protection)  against the victim and law enforcement action (Prosecutmn) to the perpetrators (traffickers)  are  realized  with  the  enactment  of Presidential  Decree  Number  88 Year  2002  on  Plan National Action Elimination of Trafficking of Women and Children (RAN P3A)Keyword.  Poverty,  Cnme.  Trajfickmg in Children